The Roots of the Obesity Boom. The Relationship Between Overweight and Educational Level Among Dutch Men, 1950–1979 - Björn Quanjer; Kristina Thompson (Historical Life Course Studies)
While in modern, high-income populations, obesity is associated with being from a low socio-economic background, this may not have always been the case. We test the relationship between obesity and educational level (as a proxy for socio-economic status) in a historical cohort of Dutch military conscripts, from the conscription years 1950–1979. We find that in the 1950s cohort, being in tertiary education was significantly associated with an increased likelihood of being overweight. In contrast, in the 1970s cohort, being in tertiary education was significantly associated with a decreased likelihood of being overweight. We find evidence that the prevalence of obesity remained broadly similar among more highly educated men, while it increased among men of a lower educational level. This likely contributed to the overall rise in the obesity rate. Our findings echo other studies that find a crossover in education’s relationship to BMI as populations become wealthier and obesity rates rise.